TINJAUAN PUSTAKA MENGENAI PENCEGAHAN DAN PEMBERANTASAN PERDAGANGAN NARKOBA DI INDONESIA - Syahar Ganji; Yusuf Setyadi (JOURNAL OF LAW AND NATION, 2022)
Many countries, including Indonesia, are concerned about increasing drug trafficking. Currently, Indonesia is in an “Emergency on Drugs Trafficking” situation. Various efforts to overcome and prevent the rampant circulation of drugs have been made to save the younger generation. Drug crimes that have spread need to be eradicated because drug trafficking has occurred nationally and has even crossed international boundaries. The purpose of this study is to identify and analyze the actions needed to prevent and overcome drug trafficking. Then, to find a final solution in dealing with obstacles that arise in the prevention and eradication of drug trafficking in Indonesia. This study uses a normative juridical approach that examines theories, concepts, legal principles, and applicable laws and regulations. In addition, it also uses an empirical approach as a supporting study to obtain more factual data. In conclusion, illicit drug trafficking has become a national and international social issue and has even become a legal issue in society. Certain legal actions are needed to prevent and resolve drug trafficking in Indonesia, one of which is through legislation. Law Number 35 of 2009 concerning Drugs is the legal basis for the prevention and eradication of drug trafficking in Indonesia. Limitation of research that focuses on the improvement and prevention of drugs must be supported by all parties from the family, community and government. and national cases that are difficult to solve considering that the network is hidden and requires special expertise where national and international cooperation is needed so that drug trafficking can be tackled quickly.